Simulasi TCP-IP Menggunakan Topologi Bus - Rafif Abyakto; Naif Baihaqi; M. Aldi Firdaus; Salsabila Aulia; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
One important technique for understanding and analyzing computer network performance is TCP/IP simulacrum. In this research, we simulate a TCP/IP network using the bus topology as a model. We use the Cisco Packet Tracer simulated network topology builder to create a bus topology and implement the TCP/IP protocol. The simulation results provide more accurate understanding of how the TCP/IP protocol functions within a bus network. We analyze network performance in terms of throughput, latency, and packet loss. The analysis's findings indicate that bus topologies have a certain amount of leeway in network operations, particularly when a collision occurs. However, this simulation offers a valuable tool to improve computer network design and management.